Association between visceral adiposity index and hyperuricemia and gout among US adults: a cross-sectional analysis of NHANES 2007–2018 - Tang, Mingjie; Li, Yinghong; Chen, Zhaoming; Yang, Jingqi (Scientific reports, 2025)
The current literature regarding the influence of the Visceral Adiposity Index (VAI) on Hyperuricemia (HUA) and gout is insufficient. This study sought to examine the correlation between VAI and the prevalence of HUA and gout. This cross-sectional analysis employed data from the National Health and Nutrition Examination Survey conducted between 2007 and 2018. Our survey data originated from the United States, with the study population consisting of U.S. adults. Visceral adiposity was evaluated using the VAI score, HUA was determined by serum uric acid concentrations, and gout was diagnosed by pertinent questionnaires. Logistic regression models were employed to investigate the relationship between VAI and the prevalence of HUA and gout. We additionally utilized restricted cubic splines (RCS), subgroup and sensitivity analyses, receiver operating characteristic curves, and threshold analysis to corroborate the findings. A total of 14,262 adult participants were included, consisting of 3025 individuals with HUA and 668 with gout. The prevalence of HUA and gout was 21.21% and 4.68%, respectively. Multivariate logistic regression analysis demonstrated a strong correlation between increasing VAI and a higher prevalence of both HUA and gout. Stratifying VAI into quartiles revealed that those in the highest quartile exhibited a markedly greater prevalence of HUA and gout relative to those in the lowest quartile, with odds ratios (ORs) of 4.17 (95% CI 3.64–4.78) and 2.04 (95% CI 1.57–2.64), respectively. The non-linear association between VAI and both situations was revealed by RCS. Threshold analysis determined 3.520 as the pivotal tipping point for HUA and 3.568 for gout. In all subgroup, increased VAI was strongly correlated with the occurrence of gout. The sensitivity analysis validated the reliability of these findings. Our investigation demonstrates a significant correlation between elevated VAI levels and a higher prevalence of HUA and gout. Maintaining optimal VAI levels may serve as a useful strategy for the prevention and management of both disorders.